Практикум модульних тестових завдань з української мови (за професійним спрямуванням) - Приблуда, Людмила Михайлівна (My University, 2018)
У навчальному посібнику представлено тестові завдання, що відбивають сучасний підхід до оцінювання навчальних досягнень студентів і відповідають вимогам навчальної програми з курсу «Українська мова (за професійним спрямуванням)». Запропоновані тестові завдання, різноманітні за формою виконання (з вибором правильної відповіді, на увідповіднення й упослідовнення), передбачають виявити рівень не лише розуміння навчального матеріалу, а й уміння аналізувати, синтезувати й застосовувати його. The tutorial presents test tasks that reflect the modern approach to assessing academic achievement of students and meet the requirements of the curriculum for the course "Ukrainian language (in professional orientation)". The proposed test tasks, diverse in the form of execution (with the choice of the correct answer, the matching and the sequence), provide for the level not only of the understanding of the educational material, but also the ability to analyze, synthesize and apply it. It is intended for students of higher educational establishments of all specialties of educational degree "bachelor" of the third (fourth) year of full-time education. The manual will be useful to anyone who wants to improve language skills, who are not indifferent to their native language and strives to become a skilled and experienced expert.
Keywords: українська мова (за професійним спрямуванням); мовна норма; тестові завдання; Ukrainian language (by professional orientation); linguistic norm; test tasks; кафедра гуманітарних дисциплін